A new Mexican Mesene (Lepidoptera, Riodinidae) - Callaghan, Curtis John; Llorente-Bousquets, Jorge; Luis-Martinez, A. (Zootaxa, 2011)
A new species of Riodinidae, Mesene jimena sp. nov., is described from the Pacific slope in southern Mexico, including notes on its habits, habitat and distribution. A comparison is made with its close relative, Mesene margaretta (A. White, 1843), found in southeastern Mexico (Atlantic slope) and Chiapas State. In addition to morphology, other criteria are discussed including behavior and related structures, spatial and temporal factors, comparison of distribution with areas of endemism and ecology. These factors were examined for the new taxon and found to confirm its status.